1997
DOI: 10.1021/bi970465a
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Glycogen Utilization, but Not Glucose Utilization, by Precontraction Glycogen Levels in Vascular Smooth Muscle

Abstract: These experiments were designed to determine whether glycogenolysis was influenced by the glycogen concentration of vascular smooth muscle. Segments of hog carotid artery smooth muscle were allowed to synthesize variable amounts of 1-[13C]glucosyl units of glycogen. Artery segments were then isometrically contracted in the presence of 2-[13C]glucose. Prior to and after isometric contraction, measurements were made of tissue glycogen content and superfusate glucose and lactate concentrations. 2-[13C]Lactate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…Thus each intermediate remains within the pathway, making it unavailable for use by other pathways in which it is also an intermediate (compartmentation). Compartmentation of glycolytic, gluconeogenic, and glycogenolytic intermediates has been shown in previous studies in our laboratory (9,(11)(12)(13) and others (1,15).…”
supporting
confidence: 74%
See 2 more Smart Citations
“…Thus each intermediate remains within the pathway, making it unavailable for use by other pathways in which it is also an intermediate (compartmentation). Compartmentation of glycolytic, gluconeogenic, and glycogenolytic intermediates has been shown in previous studies in our laboratory (9,(11)(12)(13) and others (1,15).…”
supporting
confidence: 74%
“…A 650-µl aliquot of this solution was transferred to a 5-mm NMR tube for NMR spectroscopy. 13 C-NMR was performed using a Bruker DRX 500 spectrometer. One thousand two hundred scans were acquired after sixty-four dummy scans using a 30°pulse angle at 125.77 MHz, 33,333-Hz sweep width, and 1-s predelay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results also suggest that the production of ATP for maintaining muscle contraction in vascular smooth muscles is similar to that in the bovine trachea. However, some researchers have shown that the tissue glycogen content was decreased with high K + -induced contraction in the guinea pig taenia coli [19] and porcine carotid artery [11] under aerobic conditions. More studies should be conducted to investigate the compartmentalization of the pathways of exogenous glucose and endogenous glycogen utilization for maintaining muscle contraction in smooth muscles under energy-limited conditions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some researchers have shown that glucose-free PSS or hypoxia have little effects on contraction of vascular smooth muscle, such as the aorta and carotid artery [20,23], and it has been reported that endogenous glycogen storage is used to maintain muscle contraction in the carotid artery [11,20]. However, the relationship between endogenous glycogen storage and the ability to main-tain contraction in tonic smooth muscles (such as vascular smooth muscle) in an energy limiting condition is not well known.…”
mentioning
confidence: 99%